Digital identity at the movies: understanding and designing the contemporary cinema-going experience - Styliari, Tatiana Charikleia (2019)
This thesis presents a multidisciplinary, mixed methods approach that combines Film Studies and Human Computer Interaction (HCI), aiming to elucidate the rapidly digitised cinema-going experience and its implications on the construction of cinema audiences’ digital identity. Existing literature in the field of Film Studies has looked into it from a social, economic and architectural perspective, without taking into consideration the emerging incorporation of digital practices and therefore, digital footprint within the cinema-going experience itself. HCI scholars have experimented with enriching the cinema-going experience using technological interventions but their research remains limited in the screening room space. Combining Film Studies and HCI, this research project suggests a new insight on audience research.